2009
DOI: 10.1097/yco.0b013e32832c9234
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial rehabilitation and quality of life for older adults with serious mental illness: recent findings and future research directions

Abstract: Purpose of Review The projected increase of Americans age 65 years and older will have an unprecedented impact on the health care delivery system. As a result, new models to support individuals with serious mental illness (SMI) will become increasingly more important. This selective overview highlights recent reports addressing psychosocial functioning and interventions for older adults with SMI. Recent Findings Recently published descriptive studies suggest that poor functional outcomes and lower quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
46
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 24 publications
1
46
0
1
Order By: Relevance
“…Recent reviews of published data on the rehabilitation goals for older people with serious mental illness summarized that poor outcome in social functioning and lower quality of life are strongly associated with social isolation, depression, cognitive impairment, and chronic medical illness. 1,2 The authors concluded that specific interventions are needed with regard to these specific features associated with social functioning and quality of life in older patients. Interventions should enhance social integration and involvement in meaningfulness activities and should diminish depressive symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews of published data on the rehabilitation goals for older people with serious mental illness summarized that poor outcome in social functioning and lower quality of life are strongly associated with social isolation, depression, cognitive impairment, and chronic medical illness. 1,2 The authors concluded that specific interventions are needed with regard to these specific features associated with social functioning and quality of life in older patients. Interventions should enhance social integration and involvement in meaningfulness activities and should diminish depressive symptoms.…”
mentioning
confidence: 99%
“…1 Therefore, research focusing on the impact of the age on schizophrenia features as well as on the successful treatment of these features becomes important. During the last decades, a large bulk of data was published addressing younger people suffering from schizophrenia, but the needs of older schizophrenia patients were often neglected.…”
mentioning
confidence: 99%
“…And with the "baby boom" generation now reaching age 65, the challenges and costs of treating the growing numbers of older adults with serious mental illnesses should be a major focus of patient-centered research and mental health service delivery systems. 517,521 Areas ripe for CER and PCOR to improve services to this population include (1) identifying older adults with serious mental illnesses in need of services, (2) engaging them in care, (3) determining the most effective interventions (both pharmacological and psychosocial) for this age group, (4) identifying the patient-centered outcomes valued by this group, and (5) determining how to best deliver interventions to achieve optimal patient-centered and clinical outcomes.…”
Section: Individuals In Need Of Daily Living Assistance or Social Skimentioning
confidence: 99%
“…525 Mental health treatment in nursing homes is often substandard, 518 and institutionalization is associated with worse health status, decreased availability of family supports, more severe overall symptom ratings, greater cognitive impairment, more severe functional deficits, more problem behaviors, more severe medical problems, and fewer social supports. 521 Given this, it is imperative that the mental health delivery system better understand who is a candidate for institutional care and who might be better served in other settings. Despite popular misconceptions, aging with a serious mental illness is not necessarily associated with a decline in independent functioning or with a need for institution-based long-term care.…”
Section: Individuals In Need Of Daily Living Assistance or Social Skimentioning
confidence: 99%
See 1 more Smart Citation